Effects of deforestation and riparian buffers on lotic communities in Southeastern Costa Rica: implications for biodiversity conservation in tropical streams - Lorion, Christopher M. (CATIE, Turrialba (Costa Rica), 2014)
Tesis (Ph. D.) -- CATIE, Turrialba (Costa Rica), 2007